Linking the Different Diameter Types of Aspherical Desert Dust Indicates That Models Underestimate Coarse Dust Emission - Yue Huang; Adeyemi A. Adebiyi; Paola Formenti; Jasper F. Kok (Geophysical Research Letters)
Abstract Measurements of dust aerosol size usually obtain the optical or projected area‐equivalent diameters, whereas model calculations of dust impacts use the geometric or aerodynamic diameters. Accurate conversions between the four diameter types are thus critical. However, most current conversions assume dust is spherical, even though numerous studies show that dust is highly aspherical. Here, we obtain conversions between different diameter types that account for dust asphericity. Our conversions indicate that optical particle counters have underestimated dust geometric diameter (Dgeo) at coarse sizes. We further use the diameter conversions to obtain a consistent observational constraint on the size distribution of emitted dust. This observational constraint is coarser than parameterizations used in global aerosol models, which underestimate the mass of emitted dust within 10 ≤ Dgeo ≤ 20 μm by a factor of ∼2 and usually do not account for the substantial dust emissions with Dgeo ≥ 20 μm. Our findings suggest that models substantially underestimate coarse dust emission.